Potential of Red Algae Eucheuma spinosum as Antibacterial to Pseudomonas aeruginosa - Nur Insani Amir; Arafah Nurfadillah; Tri Rama Dani (Jambura Medical and Health Science Journal, 2023)
Introduction: Eucheuma spinosum is one of Indonesia's potential marine resources that can be used as an antimicrobial. The red algae E. spinosum contains many secondary metabolites which can inhibit the growth of bacteria. This research aimed to determine the optimum inhibitory power of the red algae extract E. spinosum using n-hexane, ethyl acetate, and methanol solvents in inhibiting the growth of Pseudomonas aeruginosa bacteria.Method: The extraction process uses the maceration method with n-hexane, ethyl acetate, and methanol as solvents. Antibacterial testing was carried out using the paper disk diffusion method with soaking for 1 hour and incubating for 24 hours. The extract with the largest clear zone diameter was then tested further using Gas Chromatography-Mass Spectrometry (GCMS) to investigate the compound content in the sample.Results: The solvent that produced the largest inhibition zone diameter was ethyl acetate extract, namely 16.1 mm at a concentration of 4%. Analysis of the compounds contained in the ethyl acetate extract using GCMS showed the presence of hexadecanoic acid which is a terpenoid group.Conclusion: The optimum concentration of red algae E. spinosum extract to inhibit the growth of Pseudomonas aeruginosa was 16.1 mm in 4% ethyl acetate solvent. Key words: Antibacterial, Eucheuma spinosum, Pseudomonas aeruginosa